Makna Frasa “Ibadahmu yang Sejati” menurut Roma 12:1-2 - Arnold Manurung (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2019)
The true worship to God is the important thing for the human being. Therefore, Paul needs to be questioned about true worship in Romans 12: 1-2. And Paul tried to explain the essence of true worship, and about the agreement of Paul’s understanding of true worship according to the book of Romans 12: 1-2. This research focus on inductive text exposition method by looking at the close context and distant context. After that tried to compare the findings with the opinions of competent scholars in the field of discussion through the library research method. And finally, the writer optimistic that this paper will give the depth of the true knowledge of worship according to Romans 12: 1-2.